2015
DOI: 10.15547/bjvm.861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-hatch nutrition of arginine, lysine, methionine and threonine on performance and intestinal morphology in broiler chickens

Abstract: To investigate the effects of post-hatch nutrition of arginine, lysine, methionine and threonine on performance and intestinal morphology of broilers, 180 day-old Ross-308 were assigned to 6 treatments. Chickens were provided post-hatch (48 h) feeding of each amino-acid in 4 groups. Chickens in other 2 treated groups received no feed and water (fasting group) or just water (watering group). On day 14, performance parameters were determined, and then all chickens from each treatment were killed. After weighing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The results indicated that 0.628% digestible threonine is optimal for greater villi height. This effect may be due primarily to the direct effect of threonine on the surface area of the intestinal mucosa because threonine has higher activity in mucosal cells than does lysine or methionine (Sadrzadeh et al, 2015). Furthermore, in viscera tissues, which are drained by the portal system, threonine metabolism is higher than that of other essential amino acids (Schaart et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that 0.628% digestible threonine is optimal for greater villi height. This effect may be due primarily to the direct effect of threonine on the surface area of the intestinal mucosa because threonine has higher activity in mucosal cells than does lysine or methionine (Sadrzadeh et al, 2015). Furthermore, in viscera tissues, which are drained by the portal system, threonine metabolism is higher than that of other essential amino acids (Schaart et al, 2005).…”
Section: Discussionmentioning
confidence: 99%